Musculoskeletal Corticosteroid Administration: Current Concepts. Issue 1 (February 2019) - Shah, Amit; Mak, Davina; Davies, A. Mark; James, S.L.; Botchu, Rajesh
Numerous corticosteroid preparations are available, but the type and dose administered is frequently at the discretion of the clinician. This is often based on anecdotal evidence and experience rather than formal clinical guidelines. In order to better understand current practice, we anonymously surveyed 100 members of the British Society of Skeletal Radiologists. The results of the survey demonstrated the arbitrary use of all types of steroid preparation at different anatomical locations. In this article, we review the commonly used corticosteroids and propose a guideline to help practitioners decide on the type and dose of steroid depending on the treatment location.